Analyzing using TAM modul on primary school teachers in implementing SPPBS : Study of teachers in Kedah, Perlis and Penang - Naililhuda, Ahmad (2014)
Adaptation to the changes of information age cause educational discipline all over the world to adopt the use of information systems in the educational institutions. With this regards, Ministry of Education introduced that the School Based Assessment (PBS) as a component of the assessment conducted by the school assessment carried out by teachers of subjects continuously in the process of teaching and learning. Due to the nature of PBS as a type of continuous assessment to observe the student's development as a whole, the introduction of SPPBS application is thought to be handy for teachers to record and store the academic and non-academic data. Despite the benefit of better information management by the system, users among the teachers found the system too difficult to use and have not been able to scale down that hurdle to user acceptance and usage of the SPPBS. Therefore, this research aimed to find the determinants of system usage and relationship between system acceptance and system adoption among the primary school teachers. The data was collected through the use of survey questionnaire, distributed to 379 primary school teachers dispersed around the area of Kedah, Perlis and Penang. The result showed that the most important factor in determining teachers‟ adoption towards SPPBS was perceived of ease in using the system. There were negative correlation between perceive of usefulness and perceive of dependability towards SPPBS adoption, while there was positive correlation between perceive of ease of use and SPPBS adoption among the primary school teachers.